The Impact of Leverage on Investment: Evidence from Shariah Listed Firms - Ismail, A. G.; Ma'in, M.; Ahmat, N. (Universiti Sains Islam Malaysia, 2024)
This study examines the impact of leverage on the firm's investment decisions using information on Malaysia Shariah listed firms between 2000 and 2007. From the theory, leverage is one mechanism for overcoming the over investment problem, suggesting a negative relationship between debt and investment for firms with low growth opportunities. This paper extends the previous literature by using a panel data methodology. It shows that leverage is negatively related to investment and this impact is significant to different measures of leverage and to alternative empirical models. However, this negative effect is not significant only for firms with low growth opportunities (lower Q) but also refers to firms with high growth opportunities (high Q).